Embodiments of Evil: Gog and Magog : Interdisciplinary Studies of the "Other" in Literature & Internet Texts - Seyed-Gohrab, Asghar; Doufikar-Aerts, Faustina; McGlinn (Iranian Studies Series, 2011)
Gog and Magog, as archetypes of evil, have dwelt in our consciousness since their threatening appearance in the Bible and Quran. Maps, literature and texts ranging from Medieval Europe, the Byzantine and Arab world, in Berber, Persian and Indonesian traditions, to contemporary internet texts: all use these imaginary monstrous creatures. The figures are constantly reinterpreted as the enemies of order change. Gog and Magog have been represented with dog heads, snake tongues. On the covers of contemporary Arab apocalyptic literature they may be giants or half-humans.This volume Embodiments of Evil: Gog and Magog reveals in eight essays the images of the 'Other' in genres ranging from contemporary folk religion on the internet to the rich literary heritage of Alexander romances.